#### Answer

$=-2.1x^2+2.1x^6$

#### Work Step by Step

$y=3-0.7x^3+0.3x^7$
$y'=0-3\times0.7x^2+7\times0.3x^6=-2.1x^2+2.1x^6$

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$=-2.1x^2+2.1x^6$

$y=3-0.7x^3+0.3x^7$
$y'=0-3\times0.7x^2+7\times0.3x^6=-2.1x^2+2.1x^6$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.